El panorama nacional: apreciaciones desde un punto de vista del análisis económico del derecho - Bullard Gonzáles, Alfredo José (2023)
ADVOCATUS had the opportunity to meet with prestigious Peruvian lawyers to interview them and learn their views on various topics related to the current national scene, using an approach that considers the Law and Economics.